Efficacy of beta-blockers on blood pressure control and morbidity and mortality endpoints in hypertensives of African ancestry: an individual patient data meta-analysis - Tsabedze, Nqoba; Naicker, R. Darshni; Mrabeti, Sanaa (Frontiers in Cardiovascular Medicine, 2024)
Compared to first-line antihypertensives, beta-blockers (BB) have been reported to lower the central aortic blood pressure sub-optimally and are associated with increased stroke risk. This observation has not been investigated in hypertensives of African ancestry. We hypothesized that an individual patient data meta-analysis (IPD-MA) on the efficacy of second or third-generation beta-blockers (STGBB) in hypertensives of African descent may provide new insights. A single-stage IPD-MA analysed the efficacy of STGBB in lowering the mean arterial blood pressure and reducing the composite outcomes: cardiovascular death, stroke, and myocardial infarction. A total of 11 860 participants from four randomised control trials were included in the analysis. Second or third-generation beta-blockers reduced the mean arterial pressure by 1.75 mmHg (95% confidence interval (CI):1.16  2.33; P<0.001) in all participants included in the analysis, and by 1.93 mmHg (95% CI:0.86  3.00; P<0.001) in hypertensive Africans. In patients with established cardiovascular disease, where the benefits of BB therapy are well established, STGBB were associated with an adjusted odds ratio of 1.33 (95 % CI:1.06  1.65; P=0.015) of the composite outcome, most likely due to confounding. Similarly, the risk of total myocardial infarction was 1.76 times higher (95% CI: 1.15  2.68; P=0.008) in hypertensives of African ancestry on STGBB. Of note, STGBB reduced the mean arterial pressure comparably to other antihypertensives, and they were not associated with an increased risk of stroke.